(untitled) - Bartley, Devin M. (Rome, 2005)
The use of alien species is a proven means to increase production and value from aquatic ecosystems. In the Mekong/Lanchang basin, alien species such as tilapia (Orechromis spp.) play an important role in providing cheap and readily available protein to rural and poor sectors. However, alien species are now recognized as one of the most significant threats to aquatic biodiversity. Several steps are necessary for effective use and control of alien species, but one of the most important was identified to be following codes of practice similar to that developed by the International Council for the Exploration of the Sea.
Keywords: Fishery management,Quản lý nghề cá; Congresses,Hội nghị